Characteristics of commuter trip chains in Singapore - Palanisamy, Chandrasekar (2010)
The traditional way of describing travel behaviour has been to define trips as movements between successive activity locations. An alternative form of travel classification that encompasses the concept of travel measured in units larger than single purpose trips is known as trip chaining. Trip chaining is the linkage of consecutive trips made by one person beginning and ending at defined locations. The sequence of trips beginning and ending at home is called a home-based trip chain.